Konsep Turunan Green economy dan Penerapannya: Sebuah Analisis Literatur - M Firmansyah (Ecoplan, 2022)
The purpose of this study is to explain the determinant concept of Green economy and its application. The research was conducted qualitatively with library analysis tools. The data was obtained by browsing bibliographic sources using online search tools on the Mendeley Manager Desktop, which contains the science direct journal platform and other supporting journals. The Green economy is economic development that prioritizes environmental sustainability. A Green economy brings other concepts that become one unit: green jobs, green tourism, green financing, and investment. A Green economy can be implemented with rewards and punishments, such as pollution taxes, subsidies for waste treatment, pressure from associations, etc. Development or shifting of economic activity towards a Green economy is needed not only severe efforts by all groups to run a green-based economy, and campuses need to build curricula and conduct research and development (R and D) in the Green economy so that it becomes common knowledge.